Relationship between aerobic capacity with Birth Weight and breastfeeding patterns in children: A cross-sectional study - SILVEIRA-RODRIGUES, João Gabriel; Araújo SOARES, Gabriel; Alves LAMOUNIER, Joel; Dias SOARES, Danusa; de Oliveira DAMASCENO, Vinícius; GONÇALVES, Reginaldo (Revista de Nutrição, 2023)
Objective To analyze if aerobic capacity is related to Birth Weight and breastfeeding patterns in boys and girls, products of a term pregnancy and normal weight. Methods A representative sample of 230 Brazilian children (6-10 years old), born at term (after 37-weeks’ gestation) with normal weight (between 2.5 and 4.0kg). These children performed a Yo-Yo Test to estimate their aerobic capacity and mothers reported their children’s Birth Weight and breastfeeding patterns. The Pearson correlation coefficient was used to measure the association between aerobic capacity with Birth Weight and breastfeeding patterns. Results We did not observe any significant associations between aerobic capacity with Birth Weight and breastfeeding time in either sexes (p>0.05). Conclusion These results indicate that aerobic capacity is not related with Birth Weight or breastfeeding time in children born with normal weight and gestational age, suggesting that this complex physiological parameter does not appear to be determined by intrauterine factors that dictate the Birth Weight and breastfeeding patterns in the beginning of life.